A Study for Locations of Accident Prone on Some Provincial Roads in the West Kalimantan Province - Slamet Widodo (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2021)
Nowadays more than one million people become victim in an accident on the roads. Some efforts have already been done to reduce globally the number accident. This paper is to show the condition of some provincial roads as location study in province of Kalimantan Barat regarding with description, characteristic, and the causes of accident. The results indicate that the human error take part dominantly around of 65% accident number, meanwhile vehicle condition and road environment contribute less than 5 %. The provincial road is dominated by the two-lane two-way facility. The finding shows the frontal collision type around of 42 % on the accident number. Number of motor cycle dominate the type of vehicle on the road. It coincides with percentage of motor cycle significant involved at an accident around of 71%. The frontal collision at location of study is more than twice compared to national data. Ratio number of accidents to length of road is located on the road segment from Ketapang to Pesaguan around of 0.884 each kilometer